Wernicke Encephalopathy From Olfactory Dysfunction After COVID-19 Infection. Issue 6 (November 2021) - Landzberg, David Ross; Bery, Ekta; Chico, Suhasini; Koh, Sookyong; Weissman, Barbara
Abstract : Introduction: Coronavirus disease 2019 (COVID-19) has affected millions of people worldwide and is caused by infection from the severe acute respiratory syndrome coronavirus-2 pathogen. While COVID-19 most commonly affects the respiratory system, multiple neurological complications have been associated with this pathogen. We report a case of Wernicke encephalopathy in a young girl with poor oral intake secondary to anosmia and dysgeusia after a COVID-19 infection. Case Report: After a recent infection of COVID-19, a 15-year-old girl developed an overwhelming noxious metallic tase resulting in a 30 lb weight loss from being unable to tolerate oral foods. She presented to the hospital 3 months later with bilateral horizontal conjugate gaze palsies, up beating vertical nystagmus, difficulty with limb coordination and gait ataxia. She was found to have a thiamine level of 51 nmol/L (reference range: 70 to 180 nmol/L) and her brain magnetic resonance imaging showed fluid-attenuated inversion recovery and diffusion-weighted imaging changes in the periaqueductal gray and dorsomedial thalami suggestive of Wernicke encephalopathy. She was started on parenteral thiamine replacement and had significant neurological improvement. Conclusions: As this pandemic continues to progress, more long-term neurological sequelae from COVID-19 such as Wernicke encephalopathy can be expected. Strong clinical suspicion for these complications is needed to allow for earlier diagnosis and faster treatment initiation.